Longitudinal Academic Outcomes of Children with Secondary Attention Deficit/Hyperactivity Disorder following Pediatric Stroke. Issue 4 (19th May 2019) - Roberts, Samantha D.; McDonald, Kyla P.; Danguecan, Ashley; Crosbie, Jennifer; Westmacott, Robyn; Andrade, Brendan; Dlamini, Nomazulu; Williams, Tricia S.
ABSTRACT: The current longitudinal study examined academic outcomes of children diagnosed with secondary attention deficit-hyperactivity disorder (S-ADHD) following stroke in comparison to children with stroke-only and children with developmental ADHD (D-ADHD), and explored potential predictors of progress in these groups. We followed 55 children (n = 17 S-ADHD, n = 18 stroke-only, and n = 20 D-ADHD) over approximately four years. Children with S-ADHD and D-ADHD were more likely to have a comorbid learning disability, but children with S-ADHD were more likely to have declines in their reading scores over time. No individual or neurological factors accounted for declines. Math scores were equally likely to decline across all youth.